PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP LOYALITAS MELALUI MOTIVASI PADA PERAWAT DI RUMAH SAKIT TRIA DIPA JAKARTA - Irianti, Antania Hanjani; Tan, Pauline H. Pattyranie Tan (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The purpose of this study was to determine the effect of transformational leadership and organizational culture on motivation, and the effect of motivation on job performance. The method for the survey conducted in this study used a questionnaire. This study is a census study with a total of 78 nurses at Tria Dipa Hospital, Jakarta. Data analysis in this study used the PLS-Structural Equation Modeling (SEM) approach using SMART PLS software. The results of transformational leadership research have a positive effect on motivation, organizational culture has a positive effect on motivation and motivation positive effect on job performance. Keywords: Transformational Leadership, Organizational Culture, Motivation, Job Performance